Endometriosis in women after menopause - Kamer-Bartosińska, Anna; Szyłło, Krzysztof (Menopause Review/Przegląd Menopauzalny, 2003)
Endometriosis is a disease of unclear etiology. Studies concerning its occurrence and course most often refer to women at the reproductive age, because its frequency is the highest in this group of patients. However there is not much information about the occurrence and clinical course of endometriosis in postmenopausal women, although few reports reveal the possibility of severe complains influencing the quality of life and caused by endometriosis, or the development of this disease with no clinical symptoms. The cases with no complaints should not be ignored either due to the ability of endometriosis lesions to transform into malignant and the predisposition to some neoplasms coexistence. An analysis of bibliography concerning endometriosis occurrence in women after menopause shows that the hormonal replacement therapy, especially estrogen monotherapy should be discussed apart from several of other factors contributing to the development of the endometriosis disease. Moreover a healthy life style is also very important in postmenopausal women, because of enhanced peripheral estrogen conversion contributing to the development of endometriosis and caused not only by the age but by the obesity, so often seen in these patients, as well.